The Implementation of Gender Language Features in The Prince & Me Movie - Dewati, Niken Ayu; Wulandari, Dwi (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
Communication is essential in society, as it allows individuals to express their thoughts, intentions, and feelings, directly impacting their quality of life. Language features are the foundation of effective communication. Learning language features are essential for effective interpersonal and intercultural communication. The research entitled The Implementation of Gender Language Features (Coates 2013) in the Prince & Me Movie aims to identify language features used by male and female main characters in the Prince & Me movie. In addition, this study will examine the factors that influence the use of language features by male and female main characters. This research will fill this gap by exploring how language feature traits are related to certain factors that influence language use in the context of the movie The Prince & Me. This study analyzes the data using Coates's (2013) theory of language features and Holmes's (2013) social factor theory. This descriptive qualitative research uses the purposive sampling technique—the data collected from the Prince & Me movie (2004). The findings show that women and men used the same language features with similar frequency. According to the research, Paige, the female character, and Eddie, the male character, used the question feature the most. This study also shows that the topic is the most frequent factor that influences the utterances of female and male characters.